Evaluation of the medicinal use of clay minerals as antibacterial agents - Williams, Lynda B. (2010)
Natural clays have been used to heal skin infections since the earliest recorded history. Recently our attention was drawn to a clinical use of French green clay (rich in Fe-smectite) for healing Buruli ulcer, a necrotizing fasciitis (‘flesh-eating’ infection) caused by Mycobacterium ulcerans. These clays and others like them are interesting as they may reveal an antibacterial mechanism that could provide an inexpensive treatment for this and other skin infections, especially in global areas with limited hospitals and medical resources. Microbiological testing of two French green clays, and other clays used traditionally for healing, identified three samples that were effective at killing a broad-spectrum of human pathogens. A clear distinction must be made between ‘healing clays’ and those we have identified as antibacterial clays. The highly adsorptive properties of many clays may contribute to healing a variety of ailments, although they are not antibacterial. The antibacterial process displayed by the three identified clays is unknown. Therefore, we have investigated the mineralogical and chemical compositions of the antibacterial clays for comparison with non-antibacterial clays in an attempt to elucidate differences that may lead to identification of the antibacterial mechanism(s). The two French green clays used to treat Buruli ulcer, while similar in mineralogy, crystal size, and major element chemistry, have opposite effects on the bacterial populations tested. One clay deposit promoted bacterial growth whereas another killed the bacteria. The reasons for the difference in antibacterial properties thus far show that the bactericidal mechanism is not physical (e.g., an attraction between clay and bacteria), but by a chemical transfer or reaction. The chemical variables are still under investigation. Cation exchange experiments showed that the antibacterial component of the clay can be removed, implicating exchangeable cations in the antibacterial process. Furthermore, aqueous leachates of the antibacterial clays effectively kill the bacteria. Progressively heating the clay leads first to dehydration (200°C), then dehydroxylation (550°C or more), and finally to destruction of the clay mineral structure by (~900°C). By identifying the elements lost after each heating step, and testing the bactericidal effect of the heated product, we eliminated many toxins from consideration (e.g., microbes, organic compounds, volatile elements) and identified several redox-sensitive refractory metals that are common among antibacterial clays. We conclude that the pH and oxidation state buffered by the clay mineral surfaces is key to controlling the solution chemistry and redox related reactions occurring at the bacterial cell wall.